Tadpole-like Conformations of Huntingtin Exon 1 Are Characterized by Conformational Heterogeneity that Persists regardless of Polyglutamine Length. Issue 10 (11th May 2018) - Newcombe, Estella A.; Ruff, Kiersten M.; Sethi, Ashish; Ormsby, Angelique R.; Ramdzan, Yasmin M.; Fox, Archa; Purcell, Anthony W.; Gooley, Paul R.; Pappu, Rohit V.; Hatters, Danny M.
Abstract: Soluble huntingtin exon 1 (Httex1) with expanded polyglutamine (polyQ) engenders neurotoxicity in Huntington's disease. To uncover the physical basis of this toxicity, we performed structural studies of soluble Httex1 for wild-type and mutant polyQ lengths. Nuclear magnetic resonance experiments show evidence for conformational rigidity across the polyQ region. In contrast, hydrogen–deuterium exchange shows absence of backbone amide protection, suggesting negligible persistence of hydrogen bonds. The seemingly conflicting results are explained by all-atom simulations, which show that Httex1 adopts tadpole-like structures with a globular head encompassing the N-terminal amphipathic and polyQ regions and the tail encompassing the C-terminal proline-rich region. The surface area of the globular domain increases monotonically with polyQ length. This stimulates sharp increases in gain-of-function interactions in cells for expanded polyQ, and one of these interactions is with the stress-granule protein Fus. Our results highlight plausible connections between Httex1 structure and routes to neurotoxicity. Graphical abstract: Highlights: The physical basis for expanded polyglutamine (polyQ) neurotoxicity is unknown. HDX-MS shows a lack of stable hydrogen bonds regardless of polyQ length. Httex1 lacks stable secondary structure but contains conformationally rigid domains. Dualities are explained by tadpole-like structures with a globular polyQ domain. Surface area of polyQ domain increases with length, leading to gain-of-function interactions.